Strengthening AI and DSS Synergy for Sustainable Research: A Community Engagement for Lecturers and Researchers in Palopo - Muhammad Faisal; Nasir Usman; Emil Agus Salim Habi Talib; Medy Wisnu Prihatmono; Lisa Fitriani Ishak; Musdalifa Thamrin; Darniati Darniati; Alvina Felicia Watratan; Saharuddin Saharuddin; Muh Ilham Akbar (I-Com: Indonesian Community Journal, 2025)
The rapid development of digital technology demands a more innovative and data-driven research paradigm, yet the utilization of Artificial Intelligence (AI) and Decision Support Systems (DSS) in academic environments remains hindered by digital literacy gaps and the dominance of subjective manual methods. This community engagement program aims to introduce and strengthen participants’ understanding of the synergy between AI and DSS in supporting sustainable research in the era of digital transformation. The program employed a participatory approach through the Quadruple Helix model involving 359 participants consisting of lecturers, researchers, and practitioners. Methods included interactive lectures, technical mentoring on hybrid intelligence (integration of Machine Learning and Multi-Criteria Decision Making), and collaborative discussions via the Zoom platform. The results indicate a 35.6% improvement in participants' digital literacy, with the mean score increasing from 62.5 to 84.8. Furthermore, the technical readiness survey yielded a high score of 4.35 on a Likert scale, with participants successfully identifying practical AI–DSS applications in smart agriculture and MSME development. This program has successfully established an initial foundation for an adaptive and inclusive research ecosystem.